The abuse of entrusted power for private gain: meaning, nature and theoretical evolution - Pozsgai-Alvarez, Joseph (Crime, law and social change, 2020)
Although the study of corruption has received increasing attention over the past decades, the theoretical progress of its earlier years has been increasingly relegated to a passive comment, resulting in an underdeveloped field as a whole. To address this issue, this paper explicitly adopts a prevalent definition of corruption - i.e. the abuse of entrusted power for private gain - and explores its meaning, nature, and theoretical evolution from the earliest human bands to the present era. The result is an examination of corruption’s constitutive elements and the way they open the door for a historical account based on the social evolution of political agency and the development of increasingly specialized ethical duties. The arguments presented here aim to provide a road map for future comparative historical research on the subject, and the potential identification of social patterns which sustain corruption tolerance today.